CHANGES OF LAND USE AND LAND COVER IN SMALL ISLANDS CASE STUDY: WEH-SABANG ISLAND, INDONESIA - Arif, A.A.; Machdar,I; Azmeri; Achmad,A (Jurnal Koridor, 2019)
Development will increase sporadic land use and tend to cause land degradation. This paper is intended to investigate the effects of land use and land cover processes on Weh-Sabang Island, Indonesia. The duration of LULC changes is analyzed using Google Earth images from 2008 to 2018. Through observations of satellite imagery detected protected area and green space area has been greatly reduced in area and transformed into built-in land which functions as a tourist area and urban built environment. Where as in the coastal areas the change from vacant land to land that was built has also become larger over the past ten years. The increase in land density since 2008 is due to the construction of tourist attractions in hilly areas to coastal areas around Weh-Sabang Island, and can cause changes in the morphology and typology of the city of Sabang. Through the method of calculating the Land Diversity Index, changes can be made in the number of areas that have changed in the period of the year being monitored. The coastal areas experience more land use changes than hilly areas, and through observations of LULC changes across Weh Island, it is expected that efforts will be made to control land use changes in areas that have directly experienced land degradation, and must consider environmental control efforts. As small island like that which happened on Weh-Sabang Island. The westernmost island of the Republic of Indonesia.